Summer Employment and Tobacco Use among College Students - Rachel Hardin; Megan E. Roberts (Ohio Journal of Public Health, 2018)
Background: Research has shown that tobacco use among college students is influenced by the social environment, especially among a subset of smokers known as social smokers. Although many college campuses now have tobacco-free policies that could restrict social use of tobacco products, these policies often do not extend to common places of summer employment for college students that have similar social environments. Currently, no recommended tobacco policy exists for such summer programs, and little research has been done to assess their need. Methods: The objective of this study was to examine trends in tobacco use among the college-aged summer employees of a non-profit organization. Participants included the college-aged summer employees of a seasonal non-profit organization based in the Appalachian region from May through August 2015. At the beginning and end of the summer employment period, an online cross-sectional survey was distributed to each eligible staff member to examine trends in tobacco use. Results: Among the 60 follow-up respondents, 22.8% (n=13) reported an overall increase in tobacco use over the summer, while 3.5% (n=2) reported a decrease in tobacco use and 73.7% (n=42) reported no change. Conclusions: These results indicate that college students are at risk of increasing their tobacco use during summer employment. There is a need for further research into the role of summer workplace influences on tobacco use among college students.
Keywords: tobacco; college students; social smoking; summer employment